Multisystem Involvement with Devastating Sequelae Following Electrical Injury in a Child - A Case Report - Aman Neopane; Abhijeet Dhar; Arpita Gogoi; Reeta Bora (Indian Pediatrics Case Reports)
Background: Electrical injuries are rare but potentially devastating. The well-known complications include skin burns and neurological, cardiac, and musculoskeletal damage. Here, we report uncommon complications like acute kidney injury and blindness along with multisystem involvement in a child with electrical injury. Clinical Description: A 7-year-old developmentally normal and apparently healthy boy got electrocuted in school and presented with seizures. The child was unconscious with circulatory collapse; chest, and abdominal examination being normal. Management and Outcome: After initial resuscitation, the child was started on antiepileptic drugs (AEDs). Shock was volume responsive. Seizures were refractory and persisted beyond the 1st week, requiring many antiepileptics and mechanical ventilation. Urine output decreased, and renal functions progressively worsened with blood urea/creatinine reaching 162/6.7 mg/dl by day 2, following which he was hemodialyzed. Suspecting pigment nephropathy, urine was checked for myoglobin which was normal, and ultrasound showed normal-sized kidneys with raised echogenicity. The electrocardiogram showed sinus tachycardia initially and later tall T-waves consistent with hyperkalemia. Gradually, as the general condition and sensorium improved, he was noticed to have blindness. There was no lens dislocation, blindness being attributed to cortical cause, though brain imaging was unremarkable. The child was discharged with normal kidney functions but with severe neurological sequelae. Conclusion: The case creates awareness regarding possible derangements of serum electrolytes, renal functions, and vision in children with electrical injuries. Despite multidisciplinary care, such injuries to children can cause severe morbidity.